FOOD ADVANTAGES OF BEANS, SOYBEANS AND PEAS VARIETIES DEVELOPED BY THE SAMARA RIA - A. I. Katyuk; E. N. Shabolkina; A. V. Vasin; N. V. Anisimkina; K. A. Bulatova (Зерновое хозяйство России)
The purpose of the study is to assess the food, chemical and technological qualities of modern beans, soybeans and peas varieties developed by the Samara RIA. The study was carried out in the laboratory of the technological and analytical service of the Federal State Budgetary Scientific Institution ‘Samara Research Institute of Agriculture’ in 2014–2018. There were analyzed taste, chemical, organoleptic, technological qualities of legumes varieties. There was established high nutritional value of the beans varieties ‘Samaryankaʼ, ‘BF 12ʼ, the peas varieties ‘Flagman 9ʼ, ‘Flagman 10ʼ, ‘Flagman 12ʼ, ‘Samariusʼ, ‘Stepnyakʼ and ‘Volzhaninʼ. These beans and peas varieties had excellent taste (4–5 points), the seeds were evenly (coefficient of cooking property is 2.5) and quickly cooked (no more than 160 minutes) and had an attractive marketable state. An analysis of soybean quality showed the suitability of the varieties ‘Samer 1ʼ and ‘Samer 4ʼ for milk and cheese production, and ‘Samer 1ʼ and ‘Samer 2ʼ for butter production. It was established that all studied soybean varieties accumulated a high percentage of protein in seeds (up to 40–42%). Soya texture of these varieties added to food products will ensure protein balance. According to the content of essential amino acids in protein of legume seeds, soybean was the best. However, the proportion of essential amino acids in the total amino acid composition (essential and non-replaceable) was high in beans and peas (38 and 37%). The proportion in soybeans was 34%. The peas varieties ‘Flagman 9ʼ and ‘Flagman 10ʼ, the beans line ‘BF 12ʼ and the variety ‘Bezenchukskaya belayaʼ, the soybean variety ‘Samer 2ʼ had the largest amount of essential amino acids among other beans, peas and soybean varieties. The studied legume varieties can be used as the breeding sources for seed quality.